Silicon negative electrode material and preparation method thereof, negative electrode plate, secondary battery and electric equipment

By using a combination of nanofibers and amorphous silicon particles in the silicon negative electrode material, the problem of low efficiency and large expansion of the silicon negative electrode material during the deintercalation process is solved, and the cycle performance and life of the battery are significantly improved.

CN119725416APending Publication Date: 2025-03-28CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311277421.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The silicon negative electrode material has low efficiency and large expansion during the deintercalation process of lithium, resulting in a shortened battery life and reduced performance.

Method used

A silicon negative electrode material is used to combine nanofibers and amorphous silicon particles. The nanofibers are composed of multiple carbon nanotubes. The carbon nanotubes have pores, and the amorphous silicon particles are attached to the pores of the nanofibers.

Benefits of technology

Through the combination of nanofibers and amorphous silicon particles, the volume expansion effect of amorphous silicon particles after lithium embedded in the reaction is alleviated, the expansion volume stress is reduced, the rupture and reformation of the SEI film is reduced, and the circulation performance and life of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725416A_ABST
    Figure CN119725416A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon negative electrode material and a preparation method thereof, a negative electrode plate, a secondary battery and electric equipment, the silicon negative electrode material comprises nanofibers and amorphous silicon particles, the nanofibers comprise a plurality of carbon nanotubes, the carbon nanotubes have pores, and pores are formed among the plurality of carbon nanotubes; the amorphous silicon particles are attached into pores of the nanofibers. The silicon negative electrode material disclosed by the invention is small in lithium intercalation and deintercalation expansion and high in lithium intercalation and deintercalation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of secondary batteries, and in particular to a silicon negative electrode material and a preparation method thereof, a negative electrode sheet, a secondary battery and an electrical device. Background Art

[0002] With the continuous development of society and the emergence of new industries, the demand for lithium-ion batteries in portable, energy storage, power and other fields has been increasing year by year. Social demand has put forward higher demands on the energy density of lithium-ion batteries, and the development of high-energy-density electrode materials is imminent.

[0003] The most commonly used silicon negative electrode material in commercial applications is graphite, but the theoretical specific capacity of graphite is low, only 372mAh / g (milliampere-hours / gram). Domestic and foreign research institutions and major battery cell suppliers have improved graphite in many aspects, including material development, battery cell design, and structural upgrade optimization. Currently, the capacity is close to the limit, and it is difficult to increase the energy density. Therefore, the development of new high-energy-density silicon negative electrode materials is a top priority.

[0004] Silicon-silicon negative electrode materials have a high specific capacity of ~4200mAh / g. In addition, silicon crust resources are abundant and the lithium deintercalation platform is low, which has attracted the attention of many researchers. However, the silicon negative electrode expands greatly (>300%) when lithium is deintercalated, which will cause a series of problems in actual use. The volume stress generated by the expansion will cause the SEI film on the negative electrode surface to rupture and reform continuously, and the lithium ions and additives in the electrolyte will be continuously consumed. The irreversible lithium loss is serious, causing the battery performance to plummet and reducing the battery life; at the same time, silicon material is a semiconductor with poor conductivity, which leads to a large impedance of the silicon negative electrode. Summary of the invention

[0005] The purpose of the present application is to provide a silicon negative electrode material, a negative electrode plate and a secondary battery to solve the problem of low efficiency of lithium insertion and extraction of silicon negative electrode and large expansion of lithium insertion and extraction leading to reduced battery life.

[0006] To achieve the purpose of this application, this application provides the following technical solutions:

[0007] In a first aspect, the present application provides a silicon negative electrode material, comprising nanofibers and amorphous silicon particles, wherein the nanofibers comprise a plurality of carbon nanotubes, the carbon nanotubes have pores, and there are pores between the plurality of carbon nanotubes; the amorphous silicon particles are attached to the pores of the nanofibers.

[0008] In one embodiment, the pores of the nanofibers are uniformly distributed.

[0009] In one embodiment, the nanofiber further includes nitrogen element, and the nitrogen element is doped in the carbon nanotube.

[0010] In one embodiment, the mass percentage of the nitrogen element in the silicon negative electrode material is 0.1%-5%.

[0011] In one embodiment, the minimum size of the pores of the carbon nanotubes is greater than the maximum particle size of the amorphous silicon particles.

[0012] In one embodiment, the inner diameter of the carbon nanotube is 20nm-90nm;

[0013] And / or, the width of the pores on the tube wall of the carbon nanotube is 20nm-90nm;

[0014] And / or, the distance between two adjacent carbon nanotubes is 20nm-90nm;

[0015] And / or, the particle size of the amorphous silicon particles is 1 nm-10 nm.

[0016] In the second aspect, the present application also provides a method for preparing a silicon negative electrode material, comprising the following steps: configuring an organic carbon source into a spinning solution; spinning the spinning solution to obtain a spinning precursor; pre-oxidizing the spinning precursor to obtain a nanofiber precursor; using a plasma device to perform two-stage sintering on the nanofiber precursor to obtain a silicon negative electrode material, wherein the silicon negative electrode material comprises nanofibers and amorphous silicon particles, wherein the nanofibers comprise a plurality of carbon nanotubes, wherein the carbon nanotubes have pores, and wherein the plurality of carbon nanotubes have pores; and the amorphous silicon particles are attached to the pores of the nanofibers.

[0017] In one embodiment, the pre-oxidation treatment of the spinning precursor includes: one of muffle furnace calcination, tubular furnace calcination and polymer low-temperature pyrolysis.

[0018] In one embodiment, the two-stage sintering of the nanofiber precursor using a plasma device comprises:

[0019] Passing inert gas and sintering at high temperature to obtain the nanofibers;

[0020] A silicon-containing gas is introduced to perform vapor deposition to obtain the amorphous silicon particles, and the amorphous silicon particles are deposited in the pores of the nanofibers to obtain the silicon negative electrode material.

[0021] In a third aspect, the present application also provides a silicon negative electrode material prepared by the method for preparing the silicon negative electrode material as described in each embodiment of the second aspect.

[0022] In a fourth aspect, the present application further provides a negative electrode plate, wherein the negative electrode plate comprises a silicon negative electrode material as described in any one of the embodiments of the first aspect or the third aspect.

[0023] In a fifth aspect, the present application also provides a secondary battery, comprising the negative electrode sheet described in the fourth aspect.

[0024] In a sixth aspect, the present application further provides an electrical equipment, comprising an electrical device and the secondary battery described in the fifth aspect, wherein the battery supplies power to the electrical device.

[0025] The silicon negative electrode material provided by the present application, the pores of the nanofibers include the pores of the carbon nanotubes themselves and the pores between multiple carbon nanotubes. The synergistic cooperation between the two gaps can alleviate the volume expansion effect of the amorphous silicon particles after the lithium insertion reaction, thereby reducing the rupture of the SEI film on the negative electrode surface caused by the expansion volume stress, reducing the consumption of lithium ions and additives in the electrolyte, and improving the irreversible lithium loss, thereby improving the cycle performance of the battery and extending the service life of the battery; at the same time, the amorphous silicon particles have high anisotropy, lithium ions can be embedded in all dimensions, the lithium deintercalation efficiency becomes higher, and the rate performance of the silicon negative electrode material is increased. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 is a partial cross-sectional view of a silicon negative electrode material of an embodiment;

[0028] Figure 2 is a flow chart of a method for preparing a silicon negative electrode material according to an embodiment;

[0029] Figure 3 The present invention is a flow chart of one of the steps in a method for preparing a silicon negative electrode material according to an embodiment.

[0030] Explanation of reference numerals: 10 - carbon nanotube, 20 - amorphous silicon particle, 31 - first pore, 32 - second pore, 33 - third pore. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there can be a central component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there can be a central component at the same time.

[0033] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in the present invention includes any and all combinations of one or more of the related listed items.

[0034] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0035] Please refer to Figure 1 , the embodiment of the present application provides a silicon negative electrode material, Figure 1 It is a partial cross-sectional view of the cross section of the silicon negative electrode material, which includes nanofibers and amorphous silicon particles 20. The nanofibers include a plurality of carbon nanotubes 10, and the carbon nanotubes 10 have pores, and there are pores between the plurality of carbon nanotubes 10. The amorphous silicon particles 20 are attached to the pores of the nanofibers.

[0036] In one embodiment, the pores of the nanofiber include a first pore 31, a second pore 32, and a third pore 33. The first pore 31 is formed by the inner wall of the carbon nanotube 10, the second pore 32 is a pore on the wall of the carbon nanotube 10, and the third pore 33 is a pore between multiple carbon nanotubes 10. Amorphous silicon particles 20 are attached to any one or more of the first pore 31, the second pore 32, and the third pore 33. The carbon nanotube 10 electrically conducts the amorphous silicon particles 20, and each carbon nanotube 10 and the amorphous silicon particles 20 together form a one-dimensional conductive network, which is conducive to increasing the conductivity of the amorphous silicon particles 20, thereby increasing the rate performance of the silicon negative electrode material.

[0037] The anisotropy of amorphous silicon particles 20 is higher than that of crystalline silicon. Lithium ions can be embedded in amorphous silicon particles 20 from all dimensions, and the efficiency of lithium extraction is improved, which significantly improves the rate performance of the battery. The expansion of lithium extraction of amorphous silicon particles 20 is much lower than that of crystalline silicon, and the irreversible thickness of the corresponding battery cell (or negative electrode sheet) is also smaller than that of crystalline silicon, which can improve the long-term life performance of silicon negative electrode. Amorphous silicon particles 20 are deposited in carbon nanotubes 10 (i.e., the first pore 31 and the second pore 32), and the inner wall of the pore of carbon nanotube 10 can limit the volume expansion of amorphous silicon particles 20. Amorphous silicon particles 20 are deposited between multiple carbon nanotubes 10 (i.e., the third pore 33), and the outer wall of multiple carbon nanotubes 10 can limit the volume expansion of amorphous silicon particles 20. At the same time, carbon nanotubes 10 can form a two-dimensional or three-dimensional conductive network for an amorphous silicon particle 20, increasing the conductivity of silicon negative electrode material.

[0038] In one embodiment, the pores of the nanofibers are evenly distributed. Optionally, the evenly distributed pores may be first pores 31 of multiple carbon nanotubes 10 with similar inner diameters; second pores 32 may be evenly distributed on the carbon nanotubes 10 and have similar pore diameters; or multiple carbon nanotubes 10 may be roughly equally spaced to form multiple third pores 33 with similar pore diameters. Evenly distributed pores allow the amorphous silicon particles 20 to be evenly deposited on the carbon nanotubes 10, and can suppress the volume expansion of the amorphous silicon particles 20 at various locations with a similar effect, making the conductivity of the amorphous silicon particles 20 more uniform, and at the same time, making the expansion stress of the lithium insertion reaction of the amorphous silicon particles 20 more evenly dispersed.

[0039] In one embodiment, the nanofibers also include nitrogen elements, which are doped into the carbon nanotubes 10. Nitrogen doping can change the local charge density of the carbon nanotubes 10, improve the electron transferability of the carbon nanotubes 10, and increase the electronic conductivity of the silicon negative electrode material. At the same time, since the local charge density distribution of the carbon nanotubes 10 changes, it is beneficial to the infiltration of lithium ions, which can reduce the interface resistance between the lithium ions and the silicon negative electrode material and increase the ionic conductivity.

[0040] In one embodiment, the mass percentage of nitrogen in the silicon negative electrode material is 0.1%-5%. When the content of nitrogen is lower than 0.1%, there is no obvious improvement effect on the conductivity of the silicon negative electrode material. When the content of nitrogen is higher than 5%, the overall skeleton structure of the carbon nanotube 10 will collapse and the number of defects will increase, resulting in reduced conductivity and structural instability of the silicon negative electrode material, which will in turn affect the cycle life of the silicon negative electrode material. Optionally, the content of nitrogen may be 1%-4%, and further may be 2%-3%, etc. Specifically, the content of nitrogen may be 0.1%, 1%, 2%, 3%, 4%, 5%, etc., without limitation. The conductivity of the silicon negative electrode material generally shows a trend of first increasing and then decreasing with the increase of nitrogen content, and the doping amount of nitrogen is selected in a moderate range of 0.1%-5%.

[0041] In one embodiment, the minimum size of the pores of the carbon nanotubes 10 is greater than the maximum particle size of the amorphous silicon particles 20. This allows the amorphous silicon particles 20 to be deposited in any pore of the carbon nanotubes 10, and the pores of the carbon nanotubes 10 can inhibit the expansion of the amorphous silicon particles 20.

[0042] In one embodiment, the pores formed by the carbon nanotubes 10 themselves are first pores 31, and the inner diameter of the first pores 31 is 20nm-90nm; and / or, the pores on the tube wall of the carbon nanotubes 10 are second pores 32, and the width of the second pores 32 is 20nm-90nm; and / or, the spacing between two adjacent carbon nanotubes 10 is a third pore 33, and the length of the third pore 33 is 20nm-90nm; and / or, the particle size of the amorphous silicon particles 20 is 1nm-10nm.

[0043] Optionally, the first pore 31 may be 30nm-80nm, further 40nm-70nm, further 50nm-60nm, etc., without limitation. Specifically, the first pore 31 may be 20nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, etc., without limitation.

[0044] Optionally, the second pore 32 may be 30nm-80nm, further 40nm-70nm, further 50nm-60nm, etc., without limitation. Specifically, the second pore 32 may be 20nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, etc., without limitation.

[0045] Optionally, the third pore 33 may be 30nm-80nm, further 40nm-70nm, further 50nm-60nm, etc., without limitation. Specifically, the third pore 33 may be 20nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, etc., without limitation.

[0046] The particle size of the amorphous silicon particles 20 refers to the average particle size thereof. Optionally, the particle size of the amorphous silicon particles 20 may be 2nm-9nm, further 3nm-8nm, further 4nm-7nm, etc., without limitation. Specifically, the particle size of the amorphous silicon particles 20 may be 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, etc., without limitation.

[0047] In one embodiment, the ratio of the size of the first pore 31, the second pore 32 or the third pore 33 to the particle size of the amorphous silicon particles 20 can be 6-40, specifically, the ratio can be 6, 10, 30, 40, etc., without limitation. The size of the first pore 31, the second pore 32 or the third pore 33 increases or the particle size of the amorphous silicon particles 20 decreases, the ratio of the size of the first pore 31, the second pore 32 or the third pore 33 to the particle size of the amorphous silicon particles 20 increases, the content of the amorphous silicon particles 20 deposited in the pores of the carbon nanotubes 10 increases, and the pores have a better effect of inhibiting the volume expansion of the amorphous silicon particles 20.

[0048] Please refer to Figure 2 and Figure 3 The present application also provides a method for preparing a silicon negative electrode material, which is specifically used for preparing the aforementioned silicon negative electrode material. The preparation method comprises the following steps:

[0049] Step S10, preparing the organic carbon source into a spinning solution.

[0050] Step S20, subjecting the spinning solution to spinning treatment to obtain a spinning precursor.

[0051] Step S30, pre-oxidizing the spinning precursor to obtain a nanofiber precursor.

[0052] Step S40, using a plasma device to perform two-stage sintering on the nanofiber precursor to obtain a silicon negative electrode material, the silicon negative electrode material includes nanofibers and amorphous silicon particles 20, the nanofibers include a plurality of carbon nanotubes 10, the carbon nanotubes 10 have pores, and there are pores between the plurality of carbon nanotubes 10; the amorphous silicon particles 20 are attached to the pores of the nanofibers (see Figure 1 ).

[0053] In one embodiment, in step S10, the organic carbon source may be one or more of polymer carbon sources such as polyacrylonitrile, polyacrylic acid, and polyperfluoroethylene propylene. The spinning solution also includes a nitrogen-containing material, and preferably, the nitrogen-containing material may be one or more of aniline, formamide, melamine, urea, and dicyandiamide. The spinning solution also includes an alcohol solvent, and the alcohol solvent may be one or more of ethanol, ethylene glycol, methanol, and polyethylene glycol.

[0054] In one embodiment, in step S20, the voltage of electrospinning can be 5kV-20kV (kilovolts), the receiving distance can be 5cm-15cm (centimeter), the propulsion speed can be 50μL / min-200μL / min (microliter / minute), and the spinning time can be 3h-15h (hour). Specifically, the voltage of electrospinning can be 5kV, 10kV, 15kV, 20kV, etc., the receiving distance can be 5cm, 10cm, 12cm, 15cm, etc., the propulsion speed can be 50μL / min, 60μL / min, 100μL / min, 200μL / min, etc., and the spinning time can be 3h, 5h, 10h, 15h, etc., without limitation.

[0055] In one embodiment, the pre-oxidation treatment may be one of muffle furnace calcination, tubular furnace calcination and polymer low-temperature pyrolysis.

[0056] In one embodiment, the temperature of the pre-oxidation treatment may be 300°C-500°C (degrees Celsius), and the treatment time may be 0.5h-2h. Specifically, the temperature of the pre-oxidation treatment may be 300°C, 350°C, 400°C, 500°C, etc., and the treatment time may be 0.5h, 1h, 1.5h, 2h, etc., without limitation.

[0057] In one embodiment, nitrogen-doped carbon nanotubes are obtained by pre-oxidation treatment. The doping of nitrogen atoms causes the electronic structure of the carbon nanotubes to change, so that the nitrogen-doped carbon nanotubes have higher conductivity than pure carbon nanotubes.

[0058] In one embodiment, step S40 includes step S41 and step S42:

[0059] Step S41, introducing inert gas and sintering at high temperature to obtain nanofibers. High temperature sintering makes the pores on the carbon nanotubes more obvious, mainly in that the pores between adjacent carbon nanotubes are more obvious, and the pores on the tube wall of a single carbon nanotube are formed.

[0060] Step S42, introducing silicon-containing gas, vapor deposition, obtaining amorphous silicon particles, and the amorphous silicon particles are deposited in the pores of the nanofibers to obtain silicon negative electrode materials. Preferably, the silicon-containing gas can be silane. Amorphous silicon particles have high anisotropy and small expansion volume. At the same time, the pores of the nanofibers can further limit the expansion of the amorphous silicon particles. The amorphous silicon particles are uniformly deposited on the nanofibers to form a well-conductive one-dimensional network.

[0061] In one embodiment, the inert gas may be one or more of Ar (argon) and N2 (nitrogen).

[0062] In one embodiment, in step S41, the sintering temperature of the nanofiber precursor can be 800°C-1200°C, the sintering time can be 1h-3h, and the power of the plasma equipment can be 50W-200W (watts). Specifically, the sintering temperature of the nanofiber precursor can be 800°C, 900°C, 1000°C, 1200°C, etc., the sintering time can be 1h, 1.5h, 2h, 3h, etc., and the power of the plasma equipment can be 50W, 100W, 150W, 200W, etc., without limitation.

[0063] In one embodiment, in step S42, the gas flux of the silicon-containing gas may be 0.01L / min-0.1L / min (liters / minute), the reaction temperature of the vapor deposition may be 350°C-550°C, and the reaction time may be 0.5h-2h. Specifically, the gas flux of the silicon-containing gas may be 0.01L / min, 0.05L / min°C, 0.08L / min, 0.1L / min, etc., the reaction temperature of the vapor deposition may be 350°C, 400°C, 450°C, 550°C, etc., and the reaction time of the vapor deposition may be 0.5h, 1h, 1.5h, 2h, etc., without limitation.

[0064] The present application also provides a negative electrode plate, which includes the silicon negative electrode material as described in any one of the above embodiments.

[0065] In one embodiment, the negative electrode sheet is formed by evenly coating the negative electrode slurry on the negative electrode current collector, and then vacuum drying and cutting the negative electrode current collector, which includes but is not limited to any one of copper foil, composite copper foil or carbon-coated copper foil.

[0066] In one embodiment, the negative electrode slurry includes a silicon negative electrode material, a carbon-based negative electrode material, a conductive agent and a binder, the conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 (carbon 60) and carbon nanotubes, without limitation; the type of binder includes one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives, without limitation; the carbon-based negative electrode material includes at least one of a graphite material and a non-graphite material, without limitation; wherein the graphite material includes at least one of natural graphite or artificial graphite, without limitation; the non-graphite material includes at least one of a hard carbon material or a soft carbon material, without limitation.

[0067] In one embodiment, the mass ratio of silicon negative electrode material to negative electrode slurry is 5%-20%, the mass ratio of conductive agent to negative electrode slurry is 0.1%-3%, the mass ratio of binder to negative electrode slurry is 1%-5%, and the compaction density of negative electrode sheet is 1.1g / cm 3 -2g / cm3 (g / cubic centimeter). Specifically, the mass ratio of silicon negative electrode material to negative electrode slurry can be 5%, 10%, 15%, 20%, etc., the mass ratio of conductive agent to negative electrode slurry can be 0.1%, 1%, 2%, 3%, etc., the mass ratio of binder to negative electrode slurry can be 1%, 2%, 3%, 5%, etc., and the compaction density of negative electrode sheet can be 1.1g / cm 3 , 1.5g / cm 3 , 1.8g / cm 3 , 2g / cm 3 Wait, no restrictions.

[0068] In one embodiment, the conductive agent is Super P (conductive carbon black), the binder is sodium carboxymethyl cellulose, and the silicon negative electrode material, natural graphite, the conductive agent and the binder are dispersed in deionized water in a mass ratio of 7:90:1.5:1.5 to prepare a negative electrode slurry, and then the negative electrode slurry is evenly coated on the copper foil current collector, and then vacuum dried and punched.

[0069] In one embodiment, the conductive agent is Super P (conductive carbon black), the binder is sodium carboxymethyl cellulose, and the silicon negative electrode material, natural graphite, the conductive agent and the binder are dispersed in deionized water in a mass ratio of 20:77:1:3 to prepare a negative electrode slurry, and then the negative electrode slurry is evenly coated on the copper foil current collector, and then vacuum dried and punched.

[0070] The present application also provides a secondary battery, which includes the above-mentioned negative electrode plate. The secondary battery can be a button battery, a soft pack battery, etc. The negative electrode plate includes the silicon negative electrode material of the embodiment of the present application, which can effectively reduce the expansion of the silicon negative electrode during lithium insertion and extraction, improve the efficiency of lithium insertion and extraction, improve the cycle performance and rate performance of the battery, and increase the service life of the battery.

[0071] The present application also provides an electrical device, including an electrical device and the above-mentioned secondary battery, wherein the secondary battery supplies power to the electrical device. The electrical device may be a car, a television, a washing machine, etc., without limitation.

[0072] The technical solution of the present application is described in detail below through specific embodiments.

[0073] Example 1

[0074] This embodiment provides a silicon negative electrode material and a preparation method thereof. The silicon negative electrode material includes nanofibers and amorphous silicon particles.

[0075] The preparation method of the silicon negative electrode material comprises the following steps:

[0076] Step S10: dissolve 1 g of aniline in ethanol and stir thoroughly, then add 5 g of polyacrylonitrile and stir thoroughly to obtain a spinning solution.

[0077] Step S20: placing the spinning solution obtained in step S10 in an electrospinning machine, setting the electrospinning parameters: voltage of 20 kV, receiving distance of 15 cm, propulsion speed of 200 μL / min, spinning time of 15 h, to obtain a spinning precursor.

[0078] Step S30: placing the obtained spinning precursor into a muffle furnace for pre-oxidation treatment at a temperature of 500° C. for a treatment time of 2 h to obtain a nanofiber precursor.

[0079] Step S40: placing the obtained nanofiber precursor in a plasma device for two-stage sintering.

[0080] Step S41: In the first stage, an inert gas is introduced for high-temperature sintering and plasma pore formation. The inert atmosphere is Ar gas, the calcination time is 2h, the temperature is 800°C, and the power is 200W.

[0081] Step S42: In the second stage, silane is introduced and calcined for 0.5 h at a temperature of 500° C. and a gas flux of 0.1 L / min to obtain amorphous silicon particles by vapor deposition. The amorphous silicon particles are deposited in the pores of the nanofibers to finally obtain silicon negative electrode material.

[0082] Example 2

[0083] This embodiment provides a silicon negative electrode material and a preparation method thereof. The difference between the embodiment 1 and the embodiment 1 is that the amount of aniline added is different, and the other steps are the same. Specifically, step S10: dissolve 0.1 g of aniline in ethanol, stir well, then add 5 g of polyacrylonitrile and stir well to obtain a spinning solution.

[0084] Example 3

[0085] This embodiment provides a silicon negative electrode material and a preparation method thereof. The difference between the embodiment 1 and the embodiment 1 is that the ventilation time and ventilation volume of silane are different, and the other steps are the same. Specifically, step S42: the second stage is introduced with silane, calcined for 1h, the temperature is 500°C, the gas flux is 0.5L / min, and vapor deposition is performed to obtain amorphous silicon particles, and the amorphous silicon particles are deposited in the pores of the nanofibers to finally obtain a silicon negative electrode material.

[0086] Example 4

[0087] This embodiment provides a silicon negative electrode material and a preparation method thereof. The difference between the embodiment 1 and the embodiment 1 is that the ventilation time and ventilation volume of silane are different, and the other steps are the same. Specifically, step S42: silane is introduced into the second stage, calcined for 0.2h, the temperature is 500℃, the gas flux is 0.2L / min, and vapor deposition is performed to obtain amorphous silicon particles, and the amorphous silicon particles are deposited in the pores of the nanofibers to finally obtain a silicon negative electrode material.

[0088] Example 5

[0089] This embodiment provides a silicon negative electrode material and a preparation method thereof. The difference between this embodiment and the embodiment 1 is that the power of the first stage of introducing an inert gas for high-temperature sintering and achieving plasma pore formation is different. Specifically, step S41: the first stage of introducing an inert gas for high-temperature sintering and achieving plasma pore formation, the inert atmosphere is Ar gas, calcination for 2h, temperature is 800°C, and power is 100W.

[0090] Comparative Example 1

[0091] This comparative example provides a silicon negative electrode material.

[0092] Compared with Example 1, the material provided in Comparative Example 1 is a commercial silicon nanomaterial and does not include carbon nanotubes.

[0093] Comparative Example 2

[0094] This comparative example provides a silicon negative electrode material and a preparation method thereof. The preparation method provided in comparative example 2 is compared with that in embodiment 1, but does not include step S41.

[0095] Comparative Example 3

[0096] This comparative example provides a silicon negative electrode material and a preparation method thereof. The preparation method provided in comparative example 2 is different from that in Example 1, except that the treatment process in step S42 is different. Specifically, step S42: silane is introduced into the second stage, calcined for 3 hours, the temperature is 800°C, the gas flux is 0.01L / min, and vapor deposition is performed to obtain crystalline silicon particles, which are deposited in the pores of the nanofibers to finally obtain a silicon negative electrode material.

[0097] The relevant information of the silicon negative electrode materials provided in the above Examples 1-5 and Comparative Examples 1-3 is shown in Table 1 below.

[0098] Table 1

[0099]

[0100] Comparing Example 1 and Example 2 in Table 1, when the aniline content in the spinning solution in step S10 is reduced from 1g to 0.1g, the nitrogen content of the silicon negative electrode material is reduced from 3.0% to 0.5%. The content of the nitrogen-containing material determines the doping amount of the nitrogen element in the carbon nanotubes. The nitrogen atom replaces the carbon atom at a certain position on the carbon nanotube. When the nitrogen atom acts as a donor for doping, the number of electrons in the system increases, the electron cloud density around the nitrogen atom and the local curvature of the carbon nanotube are changed, and then the electronic structure of the system is changed, so that it has good electronic conductivity.

[0101] Comparing Example 1 and Examples 3-4 in Table 1, when the silane gas flux and ventilation time in the vapor deposition of step S42 are changed, the deposition amount and particle size of the amorphous silicon particles will change; when the silane gas flux is increased from 0.1L / min to 0.5L / min, the particle size of the amorphous silicon particles increases from 2nm to 10nm, the silane gas flux increases, the particle size and deposition amount of the amorphous silicon particles increase, and the deposition uniformity of the amorphous silicon particles in the pores of the nanofibers decreases; when the silane gas flux and ventilation time are reduced, the deposition amount decreases.

[0102] Comparing Example 1 and Example 5 in Table 1, when the plasma power in step S41 is reduced, the inner diameter of the carbon nanotube is reduced from 60nm to 20nm, the plasma power is weakened, the pore-forming effect is reduced, the content of amorphous silicon particles deposited inside the carbon nanotube and on the tube wall is reduced, and the specific capacity is reduced.

[0103] The silicon negative electrode materials provided in the above-mentioned Examples 1-5 and Comparative Examples 1-3 were respectively assembled into button-type batteries and soft-pack batteries according to the following methods.

[0104] Button cell battery includes:

[0105] Negative electrode: The silicon negative electrode material prepared in the embodiment and the comparative example was dispersed with Super P and sodium carboxymethyl cellulose in a mass ratio of 7:1.5:1.5 in deionized water to prepare a negative electrode slurry. The negative electrode slurry was evenly coated on a copper foil current collector, vacuum dried at 110°C overnight, and then punched into sheets, cut into small discs with a diameter of 1.5 cm, to obtain negative electrode sheets.

[0106] Positive electrode: Lithium electrode.

[0107] Diaphragm: PE / PP film.

[0108] Electrolyte: Ethylene carbonate and ethyl methyl carbonate are mixed in a volume ratio of 3:7, and LiPF6 (lithium hexafluorophosphate) is added to form an electrolyte, and the concentration of LiPF6 is 1 mol / L (mole / liter).

[0109] Button cell: Assemble button cells in an inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.

[0110] Soft-pack battery: Assemble the soft-pack battery in an inert atmosphere glove box in the order of negative electrode plate - separator - electrolyte - positive electrode plate - shell.

[0111] The electrochemical properties of the button cells assembled in the above examples and comparative examples were subjected to cycle stability tests and EIS (electrochemical impedance spectroscopy) tests, and the test conditions were as follows:

[0112] Cycle stability test: Place the battery in a blue power test cabinet for charge and discharge, with a charge and discharge current of 0.5mA (milliampere) and a voltage range of 0.005V-1.5V.

[0113] EIS test: tested on a Gammary electrochemical workstation, the battery was discharged to 50% SOC (battery state of charge), and the test frequency was 100KHz-0.05Hz (Hertz).

[0114] The test results are shown in Table 2 below.

[0115] Table 2

[0116]

[0117] Note: mAh / g is milliampere hour per gram, mohm is milliohm.

[0118] Comparing Example 1 and Example 2 in Table 2, when the doping content of nitrogen element is reduced, the conductivity of the silicon negative electrode material is weakened, the EIS impedance of the battery increases, and the cycle performance deteriorates;

[0119] Comparing Example 1 and Example 3 in Table 2, when the amorphous silicon particles increase, the deposition uniformity will decrease, the silicon deposition amount will increase, the battery's charge capacity will increase, but the material impedance will increase, and the battery's cycle decay;

[0120] Comparing Example 1 and Example 4 in Table 2, when the amorphous silicon particles are appropriate, the amorphous silicon particles are deposited relatively uniformly and the performance is better;

[0121] Comparing Example 1 and Example 5 in Table 2, when the inner wall porosity of the carbon nanotubes decreases, the content of deposited amorphous silicon particles decreases, the specific capacity decreases, and the inhibitory effect on silicon volume expansion decreases, but the reduction in the diameter of the carbon nanotubes has no obvious deterioration in the material impedance.

[0122] Comparing Example 1 and Comparative Example 1 in Table 2, when there is only silicon material in the silicon negative electrode material, the expansion performance of the silicon negative electrode material is large. After repeated deintercalation, the active silicon material will be pulverized and inactivated and fall off the current collector. The volume stress generated by the expansion will cause the continuous rupture and reformation of the SEI film on the negative electrode surface, continuously consume lithium ions and additives in the electrolyte, and cause serious irreversible lithium loss, resulting in the deterioration of the battery's cycle performance and rate performance.

[0123] Comparing Example 1 and Comparative Example 2 in Table 2, when the amorphous silicon particles in the silicon negative electrode material are layered in the non-porous fibers, the expansion inhibition effect on the amorphous silicon is weak and the cycle life is reduced.

[0124] Comparing Example 1 and Comparative Example 3 in Table 2, when crystalline silicon is used as a replacement, the expansion effect of crystalline silicon is stronger and the cyclability becomes weaker.

[0125] In summary, uniform pores are formed on single carbon nanotubes and nanofibers formed by multiple carbon nanotubes through inert plasma treatment and nitrogen doping is achieved. Amorphous silicon particles are formed in the uniform pores of nanofibers through vapor deposition. Lithium ions can be embedded in all dimensions, and the efficiency of lithium extraction becomes higher. The pores can limit the expansion of lithium extraction. The pores of nanofibers can limit the expansion of lithium extraction, reduce the rupture of the SEI film on the negative electrode surface caused by the volume stress generated by the expansion, reduce the consumption of lithium ions and additives in the electrolyte, and improve the irreversible lithium loss, thereby improving the cycle performance and rate performance of the battery and extending the service life of the battery. The cycle and rate performance can be significantly improved.

[0126] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0127] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A silicon negative electrode material, characterized in that: include: Nanofibers, comprising a plurality of carbon nanotubes, wherein the carbon nanotubes have pores, and there are pores between the plurality of carbon nanotubes; Amorphous silicon particles are attached in the pores of the nanofibers.

2. The silicon negative electrode material according to claim 1, characterized in that: The pores of the nanofibers are evenly distributed.

3. The silicon negative electrode material according to claim 1, characterized in that: The nanofiber further comprises nitrogen element, and the nitrogen element is doped in the carbon nanotube.

4. The silicon negative electrode material according to claim 3, characterized in that: The mass percentage of the nitrogen element in the silicon negative electrode material is 0.1%-5%.

5. The silicon negative electrode material according to claim 1, characterized in that: The minimum size of the pores of the carbon nanotubes is greater than the maximum particle size of the amorphous silicon particles.

6. The silicon negative electrode material according to claim 5, characterized in that: The inner diameter of the carbon nanotube is 20nm-90nm; And / or, the width of the pores on the tube wall of the carbon nanotube is 20nm-90nm; And / or, the distance between two adjacent carbon nanotubes is 20nm-90nm; And / or, the particle size of the amorphous silicon particles is 1 nm-10 nm.

7. A method for preparing a silicon negative electrode material, characterized in that: The steps include: preparing an organic carbon source into a spinning solution; The spinning solution is subjected to spinning treatment to obtain a spinning precursor; Performing a pre-oxidation treatment on the spinning precursor to obtain a nanofiber precursor; The nanofiber precursor is subjected to two-stage sintering using plasma equipment to obtain a silicon negative electrode material, wherein the silicon negative electrode material includes nanofibers and amorphous silicon particles, wherein the nanofibers include a plurality of carbon nanotubes, wherein the carbon nanotubes have pores, and pores are formed between the plurality of carbon nanotubes; and the amorphous silicon particles are attached to the pores of the nanofibers.

8. The method for preparing a silicon negative electrode material according to claim 7, characterized in that: The spinning precursor is subjected to a pre-oxidation treatment, which includes: one of muffle furnace calcination, tubular furnace calcination and polymer low-temperature pyrolysis.

9. The preparation method according to claim 7, characterized in that: The method of using a plasma device to perform two-stage sintering on the nanofiber precursor comprises: The first stage is sintering, in which an inert gas is introduced to obtain the nanofibers; In the second stage of sintering, silicon-containing gas is introduced to perform vapor deposition to obtain the amorphous silicon particles, and the amorphous silicon particles are deposited in the pores of the nanofibers to obtain the silicon negative electrode material.

10. A silicon negative electrode material prepared according to the method for preparing a silicon negative electrode material according to claims 7-9.

11. A negative electrode plate, characterized in that: The negative electrode plate comprises the silicon negative electrode material as described in any one of claims 1 to 6 or as described in claim 10.

12. A secondary battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 11.

13. An electrical equipment, characterized in that: The invention comprises an electric device and the secondary battery as claimed in claim 12, wherein the battery supplies power to the electric device.